2001
DOI: 10.1073/pnas.111005198
|View full text |Cite
|
Sign up to set email alerts
|

Homologous genetic recombination as an intrinsic dynamic property of a DNA structure induced by RecA/Rad51-family proteins: A possible advantage of DNA over RNA as genomic material

Abstract: Heteroduplex joints are general intermediates of homologous genetic recombination in DNA genomes. A heteroduplex joint is formed between a single-stranded region (or tail), derived from a cleaved parental double-stranded DNA, and homologous regions in another parental double-stranded DNA, in a reaction mediated by the RecA͞Rad51-family of proteins. In this reaction, a RecA͞ Rad51-family protein first forms a filamentous complex with the single-stranded DNA, and then interacts with the double-stranded DNA in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 107 publications
3
41
0
Order By: Relevance
“…We previously showed that the recognition of homology in duplex DNA by the single strand in the Rad51 filament requires the breathing of base pairs, particularly A⅐T base pairs, in the duplex DNA (19). That mechanism of recognition plus the ability of Rad51 to form paranemic joints implies that the nucleoprotein filament provides an extended catalytic surface that can promote breathing and subsequent homologous recognition anywhere along the length of the DNA molecules involved.…”
Section: Mechanism Of Recognition Of Homologymentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that the recognition of homology in duplex DNA by the single strand in the Rad51 filament requires the breathing of base pairs, particularly A⅐T base pairs, in the duplex DNA (19). That mechanism of recognition plus the ability of Rad51 to form paranemic joints implies that the nucleoprotein filament provides an extended catalytic surface that can promote breathing and subsequent homologous recognition anywhere along the length of the DNA molecules involved.…”
Section: Mechanism Of Recognition Of Homologymentioning
confidence: 99%
“…18). Solution of the structure of the single strand has shown that the bases, whose axial spacing is 50% greater than in B-form DNA, are stacked alternately with the deoxyribose moieties of the phosphodiester backbone, a configuration that links the angular displacement of bases to a change in the pucker of the sugar (19). Recent studies of human Rad51 indicate that the filament formed on single-stranded DNA provides a catalytic surface, which, on collision with duplex DNA, promotes the opening of base pairs to check for homology at the point of contact anywhere along the filament (20).…”
mentioning
confidence: 99%
“…Takehiko Shibata discussed NMR studies revealing the basis for the extended structure of ssDNA within the filaments of RecA or its yeast homolog Rad51 (55). Charles Radding reviewed the current understanding of the most critical and still mysterious step of recombinational repair, the RecA-catalyzed homology search with subsequent strand exchange.…”
Section: Homologous Recombination In Phage T4mentioning
confidence: 99%
“…Following homologous pairing of the invading DNA strand with its double-stranded counterpart, RecA protein initiates the exchange of DNA strands that results in a heteroduplex DNA with the formation of a D-loop (DasGupta et al, 1980). Currently there is no established mechanism to explain how RecA allows the invading DNA chain to displace one of the strands of fully base-paired double-stranded DNA (Shibata et al, 2001). The most important feature of this process for our purpose is that RecA-mediated exchange of DNA strands can tolerate, at a low frequency, DNA lesions or mismatched base pairs during pairing (Bianchi and Radding, 1983;Bazemore et al, 1997) and thereby alter base pairs in a targeted sequence.…”
Section: Introductionmentioning
confidence: 99%